Cardiac thrombus with risk of fulminant pulmonary embolism in paediatric antiphospholipid syndrome - Albinski, M.; Hufnagel, M.; Schelling, J.; Fleck, T.; Siepe, M.; Zieger, B.; Stiller, B. (Klinische Pädiatrie, 2016)
Antiphospholipid Syndrome (APS) describes a systemic disease caused by autoantibodies to membrane components. Involving coagulation pathways, complement factors and immune cells, it results in thrombosis in any blood vessel. Its clinical presentation varies considerably depending upon the organ affected. Paediatric data on APS remain sparse. Most case reports focus on catastrophic APS with multiple small-vessel occlusions and a life-threatening course. Here, we report on a 15-year-old patient with deep vein thrombosis and a right ventricular tumour posing the risk of a fulminant pulmonary embolism. The tumour was surgically removed. Histology revealed it to be a thrombus. The patient fully recovered and is currently treated with long term anticoagulation.
Keywords: paediatric antiphospholipid syndrome; pulmonary embolism; thrombocytopenia; venous thrombosis